The impact of cooperative learning strategies on learning some offensive basketball skills for female students. - Jabbar, Asst.L. Nishtiman Mohammed (Sulaimani Journal for Humanities, 2025)
Education is an important institution in building the future generation, enabling them to face life and providing them with sufficient experience in managing institutions in various fields and practicing the work they learned and acquired during their education. Modern teaching methods have been developed to help achieve educational goals aimed at developing the student's personality in all aspects. This learning comes through following scientific and organized methods in the teaching methods and techniques used by teachers to engage the learner and highlight their positive role, thus increasing the learner's motivation. Physical education is an integral part of general education, providing the learner with sports sciences and enabling them to perform in all sports activities so that they become a future player with experience in practice and performance, thus becoming an athlete and a champion in their specialized sport. Here, there must be appropriate teaching and educational strategies, theories, and methods that pertain to sports activities, including individual and team activities, and learning that helps in correct education and develops the cognitive level of the learner. Therefore, we find that the cooperative learning strategy is one of the important strategies in education. As for the research objectives, they are to identify the effect of the cooperative learning strategy on some offensive basketball skills for female students between the results of the pre- and post-tests for the two groups. This study aimed to identify the impact of the cooperative learning strategy on some offensive basketball skills among female students, comparing the results of the post-tests for the two groups. The research methodology involved selecting the research population from second-year female students in the Basic Education Department at the College of Physical Education and Sports Sciences, University of Sulaimani, for the academic year 2024-2025. The population consisted of 62 students (male and female). Female students were excluded from the sample as the researcher was conducting the study exclusively on female students. Ten students from section A were randomly selected for the experimental group, and ten students from section B were randomly selected for the control group. The sample size was 11.11% of the original population. To ensure equivalence, students who participated in the pilot study or who did not attend regularly were excluded. The two groups were then compared to the experimental group in terms of basketball skills. The researcher concluded that the cooperative learning strategy proved effective in teaching basketball skills (shooting, free throws, and passing) to the experimental group, as demonstrated by the results of the pre-tests and post-tests. The cooperative learning strategy proved effective in teaching basketball skills (shooting, free throw, and passing) to the experimental group in the research sample, as demonstrated in the post-tests. The same method also proved effective in teaching basketball skills (shooting, free throw, and passing) to the control group in the research sample, but to a lesser extent, between the pre- and post-tests.